Analysis of Corporate Communication Strategies in Enhancing Company Image - Feldiansyah, Feldiansyah (PERSPEKTIF, 2024)
This research has the main objective to investigate how PT. XYZ utilizes social media as a means to improve its corporate image. This research adopts a descriptive qualitative approach with an in-depth focus on PT XYZ. We analyzed the various communication strategies they implemented, including the application of P.E.N.C.I.L.S and RPAE theories, as well as conducted a SWOT analysis to identify the strengths, weaknesses, opportunities, and threats faced by the company. In addition, we also conducted surveys and interviews with the corporate communication department. The results revealed that PT XYZ succeeded in building a positive image by implementing an effective corporate communication strategy. This strategy includes Corporate Social Responsibility (CSR) activities, quality service, social and environmental responsibility, and attention to safety. In addition, we found that PT XYZ is also active in customer acquisition (CA) strategies on social media platforms, such as Twitter, regardless of the company's reputation. Information strategies are used more often than response and engagement. However, some experts argue that engagement may be more effective in achieving CSR goals. In addition, CSR communication is more focused on the outcomes produced by CSR actions rather than the concrete ways such actions are taken, in line with consumer interests and expectations. In conclusion, this study provides important insights into PT XYZ's successful corporate communication strategies in building its positive image through social media. These discoveries can serve as a helpful roadmap for other companies seeking to enhance their corporate communication strategies in social media. Therefore, this study holds the promise of making a beneficial impact on advancing corporate communication practices in the ever-expanding digital era.